(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The study intend to examine the influence of provided resources, consultant expertise, and top management support on critical success factors. To do that the study utilize the responses from 402 management consultant and employed statistical techniques like confirmatory factor analysis for ensuring the reliability and validity, and structural equation modeling for hypotheses testing. The findings revealed that provided resources, top management support, consultant expertise have a positive and statistical significant effect on critical success factors of consulting engagements. Out of that the top management support emerged as the most influential factor, emphasizing the critical role that leadership commitment plays in aligning consulting projects with organizational objectives and ensuring successful implementation.